Gene Expression Microarray Data Identify Hub Genes Involved in Osteoarthritis - Zhou, Jian; Zou, Dazhi; Wan, Rongjun; Liu, Jie; Zhou, Qiong; Zhou, Zhen; Wang, Wanchun; Tao, Cheng; Liu, Tang (Frontiers in Genetics, 2022)
The present study was performed to explore the underlying molecular mechanisms and screen hub genes of OA via bioinformatics analysis. 25 OA synovial tissue samples and 25 normal synovial tissue samples from three datasets, GSE55457, GSE36700 and GSE1919, were used to reveal the DEGs of OA by R language. The GO and pathway enrichment of DEGs were conducted using DAVID. An venn diagram was built to show the potential hub genes existng in all this three datasets. STRING database was used for constructing PPI networks and submodules of DEGs. We obtained 507 up-regulated and 620 down-regulated genes using R software. Up-regulated DEGs were significantly involved immune response, intrinsic to membrane and Calcium ion binding, while down-regulated genes were mainly enriched in regulation of transcription, non-membrane-bounded organelle and DNA binding. Results of KEGG analysis indicated that the up-regulated DEGs were mainly involved cell adhesion molecules, while down-regulated DEGs were significantly involved MAPK signaling pathway. 18 intersection genes existing in all the three datasets were identified, including Nell-1, ATF3, RhoB, STC1 and VEGFA. Additionally, 10 hub genes including CXCL12, CXCL8, CCL20 and CCL4 were found in PPI network and modules construction. Identification of DEGs and hub genes associated with OA may be helpful for reveling the molecular mechanisms OA, which might promote the development of biomarkers and drug targets of OA.